LIQUIDITY OF ENTERPRISES AND ENTERPRENEURS OF THE SECTOR I- ACCOMMODATION AND FOOD SERVICES IN THE REPUBLIC OF SERBIA - Milašinović, Marko; Knežević, Snežana; Mitrović, Aleksandra (The Business of Tourism, 2021)
The aim of this paper is to determine the level and movement of liquidity of enterprises and entrepreneurs of Sector I-Accommodation and Food Services in the Republic of Serbia in the period from 2013 to 2020. For the purposes of the research, summary data on the operations of enterprises and entrepreneurs operating within the observed sector were used, which are compiled and published by the Business Registers Agency in the form of the Financial Statements Annual Bulletin. In this paper, liquidity is measured by the current ratio, the quick ratio, the cash ratio and the net working capital. It was found that, with the fluctuations present during the observed period, both enterprises and entrepreneurs are characterized by a low value of liquidity indicators, ie the values ​​of these indicators are below the limit. Also, the research shows that the value of the used liquidity indicators is, to a large extent, at a slightly higher level among entrepreneurs compared to enterprises.
Keywords: liquidity; ratio indicators; enterprises; entrepreneurs; Sector I-Accommodation and Food Services; Republic of Serbia